Comparative Study on Quality Parameters of Royal Jelly, Apilarnil and Queen Bee Larvae Triturate - Rodica MARGAOAN; Liviu Alexandru MARGHITAS; Daniel Severus DEZMIREAN; Otilia BOBIS; Victorita BONTA; Corina CATANA; Adriana URCAN; Carmen Ioana MURESAN; Mirela Gabriela MARGIN (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Animal Science and Biotechnologies, 2017)
Given their beneficial effects in terms of health, the natural products, especially beehive products, have drawn the attention of consumers since long time ago. In order to guarantee the quality of these products on the market, their chemical composition needs to be analyzed. Thus, this current research had as objective the establishment of quality parameters for beehive brood food derived products: apilarnil and queen bee larvae triturate. These two products were compared with royal jelly which is the basis of brood food in the first 3 days of larval stage. The carbohydrates were determined by HPLC-IR and allowed the identification of seven carbohydrate compounds, predominantly glucose, fructose and sucrose. The lipid profile was analyzed by the Soxhlet method. The total protein content was determined by the Kjeldahl method. Free amino acids were analyzed by LC-MS. A total of 31 amino acids were identified of which nine are essential amino acids for humans.Â